Alternative Energy Sources on Digital Comic Media - Adnyani, Komang Alit Darma; Wibawa, I Made Citra; Margunayasa, I Gede (International Journal of Elementary Education, 2021)
The availability of innovative learning media in schools is still limited, especially in the subject of the natural sciences of fourth-grade elementary school. This research aimed at developing digital comic media on the topic of alternative energy sources for fourth-grade elementary school students. This study applied the research and development (R&D) method using the ADDIE development model with the following stages: analyze, design, development, implementation, and evaluation. The subjects of this study were two lecturers as media experts, two lecturers as material experts, two teachers as practitioners, and five fourth-grade elementary school students, while the object in this study was the developed validity of the digital comic media. The data collection method was a questionnaire method by providing assessment sheets to the subjects of the study. The instrument used to measure the validity level of digital comic media was a rating scale in the form of assessment sheets compiled from experts, practitioners, and students. The data obtained were then analyzed using a percentage formula to determine the validity of digital comic media. The average percentage scores are 96% by material experts, 97% by media experts, 87% by practitioners, and 94% by fourth-grade elementary school students, with very good classifications. Based on the results, digital comic media developed on the topic of alternative energy sources is declared valid and suitable to apply in learning in fourth-grade elementary school.Â